PENGEMBANGAN MODUL PEMBELAJARAN MENULIS KARANGAN BERBASIS STRATEGI THINK-TALK-WRITE - Apryliana, Agnes; Nisa, Hany Uswatun (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: Development of Essay Writing Learning Moduls Based on Think-Talk-Write Strategy). The curriculum 13 for high school students in class X of the material taught is writing essays. The study aims to determine the development of moduls that can be used in writing essay learning based on think-talk-write (TTW) strategies and the differences in the effectiveness of learning writing essays using the module. The research use the R&D approach. Based on the results of the analysis of the needs students and teachers it can be concluded the students need special teaching materials in learning to write essays. Therefore the TTW strategy was chosen as a strategy used to develop teaching materials. The result of the effectiveness test a t score of 28, 273 and 27, 288. This proves the existence of effectiveness in using TTW astrategy based moduls. Keywords: modul, think-talk-write, writing